(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The authors modelled and compared two hybrid stepper motors (HSM) sharing identical geometrical characteristics, phase resistance, and supply voltage. One motor features a solid stator, while the other is equipped with a laminated stator. The paper details the implementation of a three-dimensional finite element method (FEM) model, which includes the calculation of the equivalent magnetic permeability in the direction perpendicular to the laminated stack. The solid motor produces higher torque than the laminated motor, making it a better choice for applications requiring high torque density at low speeds. Experimental results confirmed the findings from the numerical simulations. After calibrating the FEM model based on the numerical results, an optimisation of both motor versions was conducted.